Pengaruh Digital Leadership Terhadap Kinerja Karyawan Dimediasi oleh Perilaku Kerja Inovatif Karyawan Milenial - Farhaq, Nur Candra; Yulianti, Emma (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2024)
The digital era is an era where technology will be used frequently. Where companies will need a leader who must be able to master digital and adhere to the standards of the company, especially in the East Java area. Therefore, companies in East Java need a digital leader to help their employees improve employee performance and creativity. The aim of this research is to determine the influence of digital leadership on employee performance which is mediated by the innovative work behavior of millennial employees in East Java. The technique used was judgment sampling technique and this research consisted of 139 employees. Data was processed using a questionnaire and then using inferential statistical analysis techniques, especially Partial Least Squares (PLS) with Smart-PLS 4 software. This research shows that digital leadership has a big influence on employee performance. Employee innovative work behavior also greatly influences Digital Leadership. Innovative Work Behavior has a significant positive effect on Employee Performance. Innovative Work Behavior has a significant and positive mediating effect on Digital Leadership and Employee Performance.